SYNTHESIS OF A CHAOTIC COMMUNICATION SYSTEM SYNCHRONIZATION LEVEL CRITERION WITH AN AUXILIARY GENERATOR - PYVOVAR OLEH, PYVOVAR OLEH; GOLEVYCH, OLEG; KAMENIAR , MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Currently, the use of deterministic chaos signals in information transmission systems represents a promising area of scientific and applied research due to their properties, including wide bandwidth, noise-like behavior, high information capacity, resistance to strong interference, and the ability to synchronize signal generators on both the transmitting and receiving sides.This paper presents a simulation model of a binary information transmission system in the Matlab/Simulink environment, based on the Rucklidge nonlinear dynamic system operating in chaotic mode. During the transmission of binary messages, unidirectional chaotic synchronization of structurally identical Rucklidge systems occurs on the receiving side. Modulation of the chaotic channel oscillations is achieved by altering the bifurcation parameters of the nonlinear transmitter system. The identification of received logical levels and the information message is accomplished by determining the level of chaotic synchronization between the two nonlinear dynamic Rucklidge systems on the receiving side. The applied criterion for the similarity of the evolution of chaotic systems on both the receiving and transmitting sides determines the accuracy of logical level identification. The selection of the synchronization criterion directly impacts the system’s tactical characteristics, including immunity to interference, sensitivity to nonlinear distortions, bandwidth, and more.The evolution of chaotic generators is proposed to be compared by utilizing the energy difference of signals from driven nonlinear dynamic systems. Several implementations of the energy criterion were considered, and their impact on the parameters of information signal transmission under conditions of additive interference and nonlinear channel distortions was modeled. As a result of this research, a universal criterion for the level of chaotic synchronization is proposed, involving the normalized energy difference of the signals from the main and auxiliary driven chaotic generators across all phase variables.Research on the system model for various levels of interference and distortions has shown that the proposed criterion is weakly sensitive to additive noise up to -10 dB and nonlinear channel signal distortions, such as bilateral clipping and step changes in the transmission line up to 20%. This finding allows for the application of this method in logical level identification amid strong interference and moderate nonlinear distortions.
Keywords: deterministic chaos; chaotic synchronization; chaotic communication system; identity criterion; binary signal